Anaemia and its impact on colorectal cancer patients: how can we better optimize surgical outcomes?. Issue 5 (13th April 2021) - Roberts, Vanessa; Deftereos, Irene; Mahbub, Bilkis; Simons, Koen; Faragher, Ian; Chan, Steven T. F.; Yeung, Justin M.
Abstract: Background: Anaemia is a common manifestation of colorectal cancer (CRC). However, appropriate workup prior to surgery and the effect of anaemia on outcomes have not been well defined. This study aimed to describe preoperative anaemia incidence, investigations performed, treatment and associated complications in a CRC surgical population at a single large tertiary institution in Australia. Methods: Patients who received surgery with curative intent for CRC between 2012 and 2017 were identified from a prospectively maintained database. Demographic and clinical outcome data were analysed. Results: In total, 754 patients with CRC were included. Anaemia was found in 350 (46.4%) patients, of which 124 (35.4%) were microcytic, 20 (5.7%) were macrocytic and 206 (58.9%) were normocytic. Older patients were more likely to have anaemia (mean age 70.28 years, standard deviation (SD) 12.98 versus 64.74 years, SD 11.74). Only 89 patients (25.4%) were tested for iron deficiency, and of these, 76 (85.4%) were found to be iron deficient and 42 (47.7%) had low ferritin. Preoperative anaemia was associated with a higher incidence of postoperative complications (adjusted odds ratio (OR) 1.46, 95%, CI 1.04–2.05; P  = 0.03) and a longer length of stay (LOS; average 1.8 days; 95% CI 0.3–3.3 days). Conclusion: A significant proportion of CRC patients had anaemia and the majority were normocytic. Only a small number of anaemic patients were tested for iron deficiency. Preoperative anaemia had an adverse effect on LOS and postoperative complications. The evaluation of anaemic patients is essential in CRC patients undergoing surgery. Abstract : Normocytic is a more common finding in CRC patients than microcytic anaemia. Patients with anaemia are rarely tested for iron deficiency. Anaemic patients are more likely to have both medical and surgical postoperative complications as well as a longer LOS. Routine testing and active anaemia management may help reduce these complications.